2009
DOI: 10.1088/0256-307x/26/5/054203
|View full text |Cite
|
Sign up to set email alerts
|

Optical Switching in Silicon Nanowaveguide Ring Resonators Based on Kerr Effect and TPA Effect

Abstract: We analyze theoretically the 1×2 low-power all-optical switching in silicon nanowaveguide ring resonators (RR) based on the Kerr effect and two-photon absorption (TPA), and give a comparison between both the all-optical switches. The calculation shows that the switching power of the TPA-RR switch is 3 orders smaller than that of the Kerr-RR switch. The switching time for both the switches is about 100 ps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Also in Ref. 26, it is shown that the switching power of the Kerr-type ring switches is about three orders larger than that of the TPA-type ring switches. This is because the nonlinear phase shift caused by the Kerr effect is proportional to the self-pumping power.…”
Section: Discussionmentioning
confidence: 99%
“…Also in Ref. 26, it is shown that the switching power of the Kerr-type ring switches is about three orders larger than that of the TPA-type ring switches. This is because the nonlinear phase shift caused by the Kerr effect is proportional to the self-pumping power.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding graph for phase shift is shown in Fig. 2 and has been derived using the data of Table 1 [15][16][17]. From this figure, it is observed that only 1.2 mW of average pump power is required to get the desired phase shift of 180 0 .…”
Section: Introductionmentioning
confidence: 99%
“…S is the effective cross-sectional area of the ring, and I and P are the intensity and power of the optical pump signal, respectively. The non-linear refractive-index change (Δn) due to high intensity optical pump pulse at the working wavelength is given by [15][16][17]:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations